1996
DOI: 10.1002/(sici)1522-7146(1996)11:1<33::aid-jbt5>3.3.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NADH oxidation by 1‐methyl‐4‐phenylpyridinium analogs as the basis for the prediction of the inhibitory potency of novel compounds

Abstract: Inhibition of NADH dehydrogenase (Complex I) of the mitochondrial respiratory chain by 1-methyl-4-phenylpyridinium (MPP') and its analogs results in dopaminergic cell death. In the present study, the inhibition of mitochondrial respiration and of NADH oxidation in inverted inner membrane preparations by the oxidation products of N-methyl-stilbazoles (N-methyl-styrylpyridiniums) are characterized. These nonflexible MPP' analogs were found to be considerably more potent inhibitors than the corresponding MPP' der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…These data suggest that glucose metabolism beyond pyruvate (i.e., a decreased oxidative phosphorylation or an altered mitochondrial ROS production) is responsible for the inhibition of sustained HPV. This explanation is well in line with our study, as all inhibitors of the mitochondrial electron transport chain are suggested to result in a reduced oxidative phosphorylation in the concentrations applied (29)(30)(31)(32)(33)(34). In accordance with the observations of Wiener and Sylvester (9,13) low glucose also suppressed sustained HPV in isolated rat intrapulmonary arteries (6).…”
Section: Pharmacologic Interventions In the Isolated Rabbit Lungsupporting
confidence: 92%
“…These data suggest that glucose metabolism beyond pyruvate (i.e., a decreased oxidative phosphorylation or an altered mitochondrial ROS production) is responsible for the inhibition of sustained HPV. This explanation is well in line with our study, as all inhibitors of the mitochondrial electron transport chain are suggested to result in a reduced oxidative phosphorylation in the concentrations applied (29)(30)(31)(32)(33)(34). In accordance with the observations of Wiener and Sylvester (9,13) low glucose also suppressed sustained HPV in isolated rat intrapulmonary arteries (6).…”
Section: Pharmacologic Interventions In the Isolated Rabbit Lungsupporting
confidence: 92%
“…MPP ϩ binds to one of two ubiquinone binding sites of the NADH multienzyme complex (17,25), which is in the same domain as the rotenone and piericidin A sites. Inhibition of NADH dehydrogenase, in addition to decreasing cell respiration, decreases mitochondrial proton pumping (16) and increases free radical production, the latter effect being correlated with cell death (26).…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately it is treatable for a period by administration of dopamine, but eventually continued free radical damage lessens the effectiveness of this therapy. The meperidine analogue MPP C , when taken by humans causes increased oxygen radical formation (30) and inhibition of NADH dehydrogenase (31). Recent reports show that primary cultures of mesencephalic dopaminergic neurons exposed to MPP C could be protected from death by addition of 4 mM D-¯-hydroxybutyrate (25).…”
Section: Parkinson's Diseasementioning
confidence: 94%